Multi-Scale Extension in an Entorhinal-Hippocampal Model for Cognitive Map Building - Wang, Jiru; Yan, Rui; Tang, Huajin (Frontiers in Neurorobotics, 2021)
Neuroscience research shows that relying on internal spatial representations provided by the hippocampus and entorhinal cortex, mammals are able to build topological maps of environments and navigate. Taking inspiration from mammals’ spatial cognition mechanism, entorhinal-hippocampal cognitive systems have been proposed for robots to build cognitive maps. However, the path integration and vision processing are time-consuming, and the existing model of grid cells is hard to achieve adaptive multi-scale extension for different environments, resulting in the lack of viability for real environments. In this work, an optimized dynamical model of grid cells is built for path integration, in which the non-linearity of sigmoidal neural transfer function is utilized to enhance grid cell activity packets and recurrent weight connections between grid cells are parameterized in a more optimized way. Thus grid firing patterns with specific spatial scales can be accurately achieved for the multi-scale extension of grid cells. In addition, a hierarchical vision processing mechanism is proposed for speeding up loop closure detection. Experiment results on the robotic platform demonstrate that our proposed entorhinal-hippocampal model can successfully build cognitive maps, reflecting robot’s spatial experience and environmental topological structures.